Urbanization and Local Economic Transformation: A Case Study in Bone Regency, Indonesia - Sam'un Mukramin; Fatimah Azis; Jamaluddin Arifin; Norwaliza Abdul Wahab; Muhammad Nawir (JSW (Jurnal Sosiologi Walisongo), 2026)
Urbanization is a socio economic phenomenon that continues to develop in various regions, including Indonesia, and significantly influences local economic transformation and social change. This study examines how urbanization shapes adaptive economic strategies, social mobility, and economic conditions in Bone Regency, Indonesia. A qualitative case study approach was employed using the analytical frameworks of Miles & Huberman and Spradley. Informants were selected purposively, while data validity was ensured through triangulation techniques. The findings reveal that urbanization is driven by economic pressures, employment opportunities, accessibility, and technological development. Urbanization encourages people to adopt adaptive livelihood strategies through temporary and circular mobility between rural and urban areas. At the same time, urbanization contributes to social change, labor transformation, and increased urban economic activity. However, it also generates challenges such as urban poverty, income inequality, unemployment, congestion, and the growth of informal settlements. Therefore, sustainable policies are needed to balance urban growth, local economic transformation, and social welfare in both rural and urban areas.